Transparent window insulation film
The transparent insulation film with hollow silica shells addresses the limitations of existing films by enhancing mechanical strength and insulation effect through selective far-infrared ray shielding, maintaining transparency and reducing thermal conductivity.
Patent Information
- Application Number
- JP2021073460
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-23
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2041-04-23
AI Technical Summary
Existing transparent insulation films for windows lack sufficient mechanical strength and insulation effect, with limitations on thickness due to increased thermal conductivity and cost, leading to reduced mechanical strength and higher costs.
A transparent insulation film with hollow silica shells dispersed in a transparent adhesive layer, where the silica shells have an average outer diameter of 3 μm to 55 μm and are distributed at 0.07% to 1.7% by mass, forming a layer that shields far-infrared rays while maintaining transparency and mechanical strength.
The film provides excellent mechanical strength and sufficient heat insulation by effectively blocking far-infrared rays, while maintaining high visibility and transparency, with improved thermal conductivity and reduced thickness.
Smart Images

Figure 0007625258000003 
Figure 0007625258000004 
Figure 0007625258000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent heat insulating film for windows, and more particularly to a transparent heat insulating film for windows used as protective films for window panes for building materials such as houses and buildings, and window panes for automobiles. [Background technology]
[0002] In the fields of architecture and automobiles, there is a demand for improved insulation of window glass surfaces, which have a large amount of heat going in and out, due to the need to conserve energy, address environmental issues, and ensure the comfort of living spaces. Methods for blocking the movement of heat from inside the room to the outside air and vice versa include double-glazing, which has an air layer between the glass panes to reduce thermal conductivity, and low-emissivity glass, in which metals with low emissivity are coated on the glass surface by deposition or sputtering. Other examples include insulation films, which are films coated with paint that contains hollow particles with low thermal conductivity, and insulation films for window glass, which are vapor-deposited or sputtered with metals or metal oxides with high reflectivity against far-infrared rays (wavelengths 2.5μm to 50μm).
[0003] For example, as an example of an insulating film coated with hollow microparticles with low thermal conductivity, Patent Document 1 discloses an insulating film having an infrared shielding layer on one side of the film to block heat, and an insulating layer on the opposite side in which hollow nanoparticles made of silica shells and having an outer diameter within the range of 10 nm to 300 nm are dispersed in a transparent synthetic resin, giving the insulating layer a thermal conductivity of 2.5 W / mK or less. Patent Document 2 discloses a transparent insulation film comprising a resin composition for forming a transparent insulation layer, which contains silica microparticles surface-modified with a compound having a phenyl group, a polysilane, an ionizing radiation-curable material, and an oil-soluble azo polymerization initiator, and which is formed by coating a transparent substrate with the resin composition for forming a transparent insulation layer and curing it to form a transparent insulation layer with a large porosity, on which an adhesive is provided. Furthermore, Patent Document 3 discloses a heat insulating film having excellent heat insulating properties and transparency, in which a block copolymer layer having a porous structure with an average pore size of 5 to 1000 nm and a thickness in the range of 0.01 to 500 μm is formed on a plastic film instead of hollow silica microparticles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5810361 [Patent Document 2] Patent No. 6604053 [Patent Document 3] Patent No. 6445975 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the thermal insulation material used in building materials has a thermal conductivity of 0.1 W / mK or less, and the thermal insulation effect of the thermal insulation film of Patent Document 1 is not sufficient. Furthermore, in order to improve the thermal insulation, it is possible to increase the thickness by stacking a large number of nano hollow particles to increase the thickness and improve the thermal insulation effect, but there is a limit to increasing the thickness due to the decrease in mechanical strength, the increase in cost due to the increase in the amount of thermal insulation material used, and the increase in capacity for thermal insulation. In addition, the thermal conductivity of the transparent thermal insulation film of Patent Document 2 is very small at 0.040 W / mK to 0.056 W / mK, so the thermal insulation effect can be improved by increasing the thickness of the transparent thermal insulation layer, but since the porosity is large at 38% to 48%, there is a limit to increasing the thickness due to the decrease in mechanical strength, the increase in cost due to the increase in the amount of thermal insulation material used, and the increase in capacity for thermal insulation, as with the thermal insulation film of Patent Document 1. Furthermore, as with the thermal insulation film of Patent Document 3, there is a limit to increasing the thickness due to the decrease in mechanical strength, the increase in cost due to the increase in the amount of thermal insulation material used, and the increase in capacity for thermal insulation, as with the thermal insulation film of Patent Document 1. It is desirable for a heat insulating film for window glass to have excellent mechanical strength and a sufficient heat insulating effect, but such a film has not yet been realized.
[0006] Therefore, the present invention has been made to solve such problems, and the main object of the present invention is to provide a transparent insulation film for windows that has excellent mechanical strength and sufficient insulation effect. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to achieve the above object. As a result, in order to provide a transparent heat insulating film for windows that is excellent in mechanical strength and has sufficient heat insulating effect, they have found the relationship between the far infrared rays (wavelength 2.5 μm to 50 μm) to be shielded for heat insulation and the outer diameter of the hollow fine particles, the relationship between the thermal conductivity and the inner diameter of the partitioned particles, the relationship between the refractive index and thickness of the hollow fine particles and the adhesive, and the relationship between the refractive index and thickness of the film substrate and the glass substrate to which it is attached in order to improve the visible light transmittance by the canceling effect due to interference, and have completed the present invention.
[0008] In other words, the transparent insulating film for windows of the present invention is a transparent insulating film for bonding to a window glass substrate, and is characterized in that an insulating layer is formed on at least one side of a substrate film that transmits far infrared rays, in which hollow silica-shelled microparticles are dispersed, the internal space of which is approximately uniformly divided into spaces of 68 nm or less, and the hollow silica-shelled microparticles are dispersed in an amount of 0.07 mass% or more relative to the total solid content of the insulating layer excluding the hollow silica-shelled microparticles.
[0009] In the transparent heat insulating film for windows of the present invention, the heat insulating layer is a transparent heat insulating adhesive layer that transmits far infrared rays, and the average outer diameter of the silica shell hollow fine particles is 3 μm to 55 μm, and the silica shell hollow fine particles are preferably dispersed in an amount of 0.07 mass % to 1.7 mass % based on the total solid content of the transparent heat insulating adhesive layer excluding the silica shell hollow fine particles. In the present invention, the "outer diameter of the silica shell hollow fine particles" refers to the sphere-equivalent diameter (measured using a laser diffraction / scattering particle size distribution measuring device LA-950V2 manufactured by Horiba, Ltd., measuring particle size range: wet 0.01 μm to 3000 μm, measuring method: flow cell measurement), and the "average outer diameter" refers to the arithmetic mean value of the calculated sphere-equivalent diameter (volume basis).
[0010] In addition, in the transparent insulation film for windows of the present invention, it is preferable that the insulation layer is a transparent insulation resin layer that transmits far infrared rays, and the average outer diameter of the silica-shelled hollow fine particles is 3 μm to 55 μm, and that they are dispersed in an amount of 0.07 mass % to 1.7 mass % relative to the total solid content of the transparent insulation resin layer excluding the silica-shelled hollow fine particles.
[0011] Furthermore, in the transparent heat insulating film for windows of the present invention, the heat insulating layer preferably has a thickness of 10 to 200 μm. Effect of the Invention
[0012] According to the present invention, it is possible to provide a transparent heat insulating film for windows which has excellent mechanical strength and a sufficient heat insulating effect. [Brief description of the drawings]
[0013] [Figure 1] 1 is a cross-sectional view of a transparent heat insulating film for windows according to one preferred embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a transparent heat insulating film for windows according to another preferred embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The transparent insulating film for windows of the present invention is a transparent insulating film for bonding to a window glass substrate, and is characterized in that an insulating layer is formed on at least one side of a substrate film that transmits far infrared rays, in which hollow silica-shelled particles are dispersed, the internal space of which is approximately uniformly divided into spaces of 68 nm or less, and the hollow silica-shelled particles are dispersed in an amount of 0.07 mass% or more relative to the total solid content of the insulating layer excluding the hollow silica-shelled particles.
[0015] Generally, when a material such as a metal or ceramic with a high reflectance or absorption rate is used to block far-infrared rays by reflection or absorption, it also reflects and absorbs visible light, so if the blocking is increased by using a metal or ceramic with a high reflectance or absorption rate, visible light will also be reflected and absorbed, and the function as a window film will be lost. Therefore, if only far-infrared rays are selectively blocked, the transparency and transmittance of visible light will not be lost, but it is very difficult to achieve this with current technology. Therefore, a method for blocking only far-infrared rays without losing the transparency and transmittance of visible light was examined, and the present invention was arrived at.
[0016] When light enters a transparent material in which fine particles are dispersed, if the wavelength of the light is shorter than the size of the fine particles, it is blocked by the fine particles. However, if the wavelength is longer than the size of the fine particles, it will slip through the gap between the objects due to the diffraction phenomenon. For example, when a UV-blocking agent in which fine particles with a very small particle diameter are dispersed is irradiated with light, the ultraviolet rays, which tend to travel in a straight line, collide with the fine particles and are blocked, but the visible light, which tends to travel in a less straight line, appears transparent as it goes around the back of the fine particles due to the diffraction phenomenon. However, when the particle diameter of the fine particles becomes larger than the visible light, even if it bends a little, it cannot go around the back of the large fine particles, so the visible light is blocked as well as the ultraviolet rays. A similar phenomenon occurs with sound waves. Incidentally, diffraction is a phenomenon that occurs with all waves, including sound waves, water waves, and electromagnetic waves (visible light, X-rays, etc.), so in order to block far-infrared rays, it is sufficient to disperse fine particles larger than the wavelength of far-infrared rays in resin, etc. However, if far-infrared rays are blocked by dispersing fine particles larger than their wavelength in a resin or other material, the particle diameter of the fine particles is larger than the wavelength of visible light, so visible light is also blocked, resulting in a loss of transparency and transmittance for visible light, just as with metals and ceramics, which have a high reflectivity.
[0017] Normally, objects such as metals absorb part of the radiant heat and reflect the rest, so the following relationship between absorptance α and reflectance ρ, "α+ρ=1," holds, and it is clear that they do not transmit in the visible light and infrared bands. However, objects such as glass and plastics are gray bodies that absorb some of the radiant heat, reflect some of it, and transmit some of it. In the case of such gray bodies, the following relationship between absorptance α, reflectance ρ, and transmittance τ holds, "α+ρ+τ=1," and it is clear that they transmit in the visible light and infrared bands. In addition, according to the Beer-Lambert law below, it can be seen that the transmittance increases if the thickness of the shell is made thinner. Absorbance A=-logT=εCL (A: absorbance, T: transmittance, ε: extinction coefficient, which is a value specific to the substance, C: molar concentration of the substance in the cell solution, L: cell length (length in the direction of irradiation))
[0018] Therefore, if transparent hollow particles with a very thin shell are used instead of solid particles with high reflection and absorption, in addition to reflection on the surface of the hollow particles, the radiant heat that passes through the shell and enters the inside of the hollow particles is also reflected due to the difference in refractive index between the shell and the air layer inside, so that a transparent and high far-infrared shielding effect can be obtained. Also, when light is irradiated onto particles, the reflection is scattering, and scattering by particles smaller than the wavelength of light is called Rayleigh scattering, and scattering by particles the same as or slightly larger than the wavelength of light is called Mie scattering. Furthermore, when the size of the particles becomes larger than the wavelength of light, it can be expressed by a geometric optics approximation.
[0019] Next, we will consider ways to increase the transmittance of visible light. In general, for a smooth substrate that does not absorb light, the reflectance R when light is perpendicularly incident from medium 1 with refractive index n1 to medium 2 with refractive index n2 is expressed by the Fresnel formula below. R = [(n1-n2) / (n2+n1)] 2 As is clear from the above, for example, when medium 1 is an air layer (n1=1.00), the reflectance decreases and the amount of light transmission increases as the refractive index n2 of medium 2 approaches 1.00.
[0020] Furthermore, when an anti-reflection layer is provided on the substrate, the intensity of reflected light is basically determined by the following two conditions, taking into account the effect of optical interference by applying the Fresnel equation to each boundary surface: 1 : Phase condition; d=(1 / 4)·(λ / n2) 2 : Amplitude condition;n2 =(n1·n3) 1 / 2 (n1: refractive index of air, n2: refractive index of coating, n3: refractive index of substrate, d: film thickness (nm), λ: wavelength of incident light (nm)) If the wavelength of the incident light and the refractive index of the coating are known from the above, it is possible to determine the film thickness at which the reflectance is reduced. In principle, the reflected light from the film surface and the reflected light from the film-substrate interface interfere with each other in a destructive manner, canceling out their amplitudes and reducing the reflectance.
[0021] From the above, it can be seen that the visible light transmittance can be improved by laminating a material with a small refractive index to a specified thickness. However, if lamination is performed under the above conditions that consider only anti-reflection in order to improve the visible light transmittance, the reflection of radiant heat in the wavelength range of thermal radiation at room temperature is reduced, and the visible light transmittance is improved but the heat insulating effect is reduced. Normally, when the particles are about the size of the wavelength of light, an interference effect occurs, and when the particles become even larger, the cancellation effect due to interference becomes greater. At infinite size, cancellation is complete, there is no scattering, and it becomes completely transparent. For example, it is well known that when transparent glass is finely crushed, diffuse reflection occurs and it becomes white and opaque. Therefore, the larger the diameter of the particles is compared to the wavelength of the visible light band, the greater the cancellation effect due to interference, and the visible light band can be made transparent.
[0022] Based on these ideas, the present invention has discovered the relationship between the far-infrared rays to be blocked and the particle diameter of the hollow microparticles, the relationship between the refractive index and thickness of the hollow microparticles and adhesive, and the relationship between the refractive index and thickness of the film substrate and the glass substrate to which it is attached, in order to improve visible light transmittance through a cancellation effect due to interference, and further discovered the use of silica-shelled hollow microparticles that have a large outer diameter and have a low thermal conductivity by approximately uniformly partitioning the internal space of hollow microparticles with a large outer diameter to be smaller than the mean free path of air, 68 nm, to block far-infrared rays, thereby enabling a transparent window insulation film with high thermal insulation properties to be obtained.
[0023] The nano-hollow particles disclosed in Patent Documents 1 to 3 have an outer diameter smaller than the wavelength of visible light in order to increase transparency, and the pores of the nano-hollow particles are smaller than the mean free path of the molecules inside the hollow in order to improve heat insulation, thereby reducing the thermal conductivity. However, it cannot be said that a sufficient effect has been obtained. In this way, when hollow particles with small outer and inner diameters are stacked in multiple layers to reduce the thermal conductivity, the mechanical strength decreases, but hollow particles with large outer diameters and small internal spaces can exhibit the same thermal conductivity as those stacked in multiple layers even in a single layer, and have strong mechanical strength. Furthermore, even if several layers are stacked to further reduce the thermal conductivity, the mechanical strength is hardly reduced.
[0024] By dispersing hollow silica shell particles, the internal space of which is approximately uniformly divided into particles of 68 nm or less, in the transparent resin used in the adhesive or coating agent used in the window glass film, rather than the nano-hollow particles as in the above-mentioned patent document, in the transparent resin used in the adhesive or coating agent, far infrared rays (wavelength 2.5 μm to 50 μm) are also blocked, and the insulating effect is significantly improved.
[0025] Hereinafter, preferred embodiments of the transparent heat insulating film for windows of the present invention will be described with reference to the accompanying drawings. However, the transparent heat insulating film for windows of the present invention is not limited to these embodiments.
[0026] A cross-sectional view of a transparent heat insulating film for windows according to a preferred embodiment of the present invention is shown in Fig. 1. The transparent heat insulating film for windows 10 has a base film 1, a transparent heat insulating adhesive layer 4 in which hollow particles 3 having silica shells are dispersed in an adhesive 2, and further has a hard coat layer 5 on the opposite side of the transparent heat insulating adhesive layer 4 with the base film 1 sandwiched therebetween, with each layer laminated in this order. The base film 1 and the window glass surface can be adhered to each other via the transparent heat insulating adhesive layer 4.
[0027] A cross-sectional view of a transparent heat insulating film for windows according to another preferred embodiment of the present invention is shown in Fig. 2. The transparent heat insulating film for windows 20 has a base film 11, a transparent heat insulating resin layer 14 in which hollow silica-shelled particles 13 are dispersed in a transparent resin 12, and a hard coat layer 15, and further has an adhesive layer 16 on the opposite side of the transparent heat insulating resin layer 14 and the hard coat layer 15 with the base film 11 sandwiched therebetween, with each layer laminated in this order. The base film 11 and the window glass surface can be adhered to each other via the adhesive layer 16.
[0028] The heat flow in the transparent heat insulating window film of the present invention will be explained using Figure 1. The heat flow in the transparent heat insulating window film of the present invention is considered to be as follows. Heat that moves from inside the room to the outside air can be caused by radiation or convection, but since the purpose of this example is to block far-infrared radiation heat, the flow of radiation heat will be explained. First, far infrared rays are radiated from inside the room toward the window glass. Since the base film 1 and the adhesive 2 transmit a large amount of far-infrared rays (wavelengths of 2.5 μm to 50 μm), the far-infrared rays that have transmitted through the base film 1 also transmit through the adhesive 2 and reach the hollow fine particles 3 with silica shells. The far-infrared rays that reach the hollow silica-shell particles 3 are scattered on the surfaces of the hollow silica-shell particles 3 and radiated in all directions. A portion of the far infrared rays reflected toward the base film 1 on the incident side is absorbed by the adhesive 2 and the base film 1, and the remainder is transmitted and radiated into the room. The far-infrared rays that pass through the hollow silica-shelled particles 3 are totally reflected due to the difference in refractive index between the hollow silica-shelled particles 3 and the air inside the hollow silica-shelled particles 3, and are reflected toward the film. A portion of the far-infrared rays is absorbed by the adhesive 2 and the base film 1, and the remainder is transmitted and radiated into the room. The far-infrared rays that penetrate and enter the inside of the hollow silica-shelled fine particle 3 are scattered inside and are similarly repeated in reflection and absorption. Also, the heat absorbed inside the transparent heat insulating film for windows 10 would flow by conduction to the outside air, which has a lower temperature, but is blocked by the hollow fine particles 3 with silica shells, which have a low thermal conductivity. The heat absorbed by the hollow silica shell particles 3 is then re-radiated into the interior of the hollow silica shell particles 3, thereby performing the same action.
[0029] Each of the components constituting the transparent heat insulating film for windows of the present invention will be described in detail below.
[0030] <Hollow particles with silica shell> The silica-shelled hollow particles used in the transparent heat insulating film for windows of the present invention are water repellent, and the internal space is approximately uniformly divided into spaces of 68 nm or less. Typical physical properties of the silica-shelled hollow particles include a bulk density of 0.1 g / cm 3 ~ 0.15g / cm 3 , and thermal conductivity is 0.01 W / m K to 0.06 W / m K.
[0031] Conventional hollow particles such as silica shells are produced by dispersing hollow particles of silica shells, which have a very low density (only the silica shells, excluding micropores), in a resin, based on the knowledge that reducing the bulk density of the silica shell is necessary to obtain extremely low thermal conductivity. However, with the conventional thickness of the dispersion layer, such as about 6 μm in Patent Document 1, it is difficult to obtain a large thermal insulation effect no matter how low the thermal conductivity is.
[0032] In order to reflect far-infrared rays by causing diffuse reflection at the surfaces and interfaces of hollow particles and to take advantage of the low thermal conductivity of hollow particles, it is necessary to increase the outer diameter of the silica shell in a transparent heat insulating film for windows. However, in order to reduce the thermal conductivity of hollow particles, it is necessary to make the inner diameter smaller than the mean free path of the atmosphere, 68 nm, so that heat exchange due to gas convection or molecular motion does not occur inside the space. Normally, if the inner diameter of a hollow body is small, the outer diameter also becomes small, so diffuse reflection occurs at the surfaces and interfaces of hollow particles, making it difficult to reflect far-infrared rays.
[0033] In order to obtain both effects, we selected hollow particles with a silica shell whose outer diameter is larger than the wavelength of far-infrared light, and whose internal space is approximately uniformly divided so that it is smaller than the mean free path of the atmosphere, 68 nm. "L = (√2nσ) -1 " L: mean free path (m), n: number density of scattering sources (m -3 ), σ: effective cross section at the time of scattering (m 2 ) where the particle velocity is assumed to follow Maxwell distribution, and the mean free path of the atmosphere is calculated under the conditions when the atmospheric pressure is 1013 hPa. "The internal space is approximately uniformly divided" refers to a state in which the internal space is divided into small cellular spaces, for example, like a beehive, and "approximately uniformly divided to be smaller than 68 nm" refers to "the length, width, and height of the "cellular spaces" measured at 30 randomly selected points (from an image taken with a transmission electron microscope (manufactured by FEI COMPANY) are each 68 nm or less."
[0034] The silica-shelled hollow fine particles of the present invention are fine particles having a relatively large outer diameter in order to obtain a heat insulating effect by diffuse reflection. The average outer diameter of the silica-shelled hollow fine particles of the present invention is preferably 3 μm to 55 μm, more preferably 5 μm to 45 μm, and most preferably 5 μm to 35 μm. If the average outer diameter is 3 μm or more, the heat insulating effect of the present invention can be obtained, and if it is 55 μm or less, high visibility and transparency can be maintained.
[0035] In addition, the outer diameter range of the silica-shelled hollow fine particles of the present invention is preferably within a certain range. The outer diameter range of the silica-shelled hollow fine particles of the present invention is preferably 2 μm to 60 μm, more preferably 2.5 μm to 50 μm, and most preferably 3 μm to 40 μm. If the outer diameter range of the silica-shelled hollow fine particles of the present invention is 2 μm to 60 μm, the wavelength of far-infrared rays can be effectively blocked, and the particles can be easily dispersed in the heat insulating layer, thereby making the thickness of the layer thinner. In the present invention, the "outer diameter range of the silica-shelled hollow fine particles" refers to the minimum to maximum of the sphere-equivalent diameter (volume basis) effective for blocking far-infrared rays.
[0036] <Film substrate> The substrate film used in the transparent heat insulating film for windows of the present invention is not particularly limited as long as it can transmit far infrared rays and provide the strength required for application to a window surface. The material constituting the substrate film is not particularly limited, and may be, for example, a polyester film, a polycarbonate film, a polyacrylic film, etc. Among these, polyester films such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polyarylate are preferred because of their versatility, excellent visibility, and transparency.
[0037] The thickness of the substrate film is not particularly limited as long as the transparent heat insulating film for windows has sufficient strength, but is preferably 10 to 200 μm, more preferably 20 to 150 μm. If the thickness of the substrate film is 10 μm or more, the transparent heat insulating film for windows can have sufficient strength, and if the thickness is 200 μm or less, high visibility and transparency can be maintained even when the film is attached to glass or the like, and the film can be easily attached to window glass.
[0038] The substrate film may have one or more transparent near-infrared shielding layers.
[0039] <Thermal insulation layer> The heat insulating layer used in the transparent heat insulating film for windows of the present invention includes a transparent heat insulating adhesive layer in which hollow particles of silica shell are dispersed, or a transparent heat insulating resin layer in which hollow particles of silica shell are dispersed in a transparent resin layer, and these may be formed on one side or both sides of the film for window glass. The transparent heat insulating resin layer may be formed between the transparent heat insulating adhesive layer and the film for window glass, or may be formed on the side opposite to the transparent heat insulating adhesive layer. The heat insulating layer may be a single layer, or may be a multi-layer if necessary.
[0040] The thickness of the heat insulating layer of the present invention is large because the silica shelled hollow fine particles used in the present invention cannot be dispersed in a thickness of about 6 μm as in the dispersion layer of Patent Document 1. The thickness of the heat insulating layer of the present invention is preferably 10 to 200 μm, more preferably 20 to 100 μm. If the thickness of the heat insulating layer is 10 μm or more, the adhesive strength with glass or the like can be secured while maintaining the heat insulating effect of the present invention, and if it is 200 μm or less, high visibility and transparency can be maintained.
[0041] The heat insulating layer of the present invention contains 0.07% by mass or more of silica-shelled hollow fine particles based on the total solid content of the heat insulating layer excluding the silica-shelled hollow fine particles. By containing 0.07% by mass or more of silica-shelled hollow fine particles based on the total solid content of the heat insulating layer excluding the silica-shelled hollow fine particles, the heat insulating effect of the present invention can be obtained. In addition, it is preferable that the content of silica-shelled hollow fine particles is 0.07% to 1.7% by mass based on the total solid content of the heat insulating layer excluding the silica-shelled hollow fine particles. If the content of silica-shelled hollow fine particles is 1.7% by mass or less based on the total solid content of the heat insulating layer excluding the silica-shelled hollow fine particles, high visibility and transparency can be maintained.
[0042] <Transparent heat insulating adhesive layer and adhesive> The adhesive used to form the transparent heat insulating adhesive layer used in the transparent heat insulating film for windows of the present invention is not particularly limited in type as long as it is transparent and transmits far infrared rays, and can be any adhesive that can adhere the transparent heat insulating film for windows to the window surface. For example, any adhesive such as an acrylic adhesive, a urethane adhesive, or a silicon adhesive can be used, but considering the dispersibility of the hollow particles of silica shell, an acrylic adhesive is particularly preferably used.
[0043] The pressure-sensitive adhesive may be used alone or in combination of two or more kinds, and other components such as, for example, a tackifier, an ultraviolet absorber, an infrared shielding agent, a plasticizer, a photopolymerizable compound, a photoinitiator, a foaming agent, a polymerization inhibitor, an antiaging agent, a filler, a coupling agent, an antistatic agent, etc. may be added within a range that does not impair the object of the present invention. Note that the ultraviolet absorber, the infrared shielding agent, etc. may be contained in a transparent resin to form an ultraviolet absorber layer, an infrared shielding agent layer, etc. on the surface opposite the pressure-sensitive adhesive or between the pressure-sensitive adhesive and the film surface.
[0044] As described above, the thickness of the transparent heat insulating adhesive layer is preferably 10 to 200 μm, more preferably 20 to 100 μm. If the thickness of the transparent heat insulating adhesive layer is 10 μm or more, the adhesive strength with glass or the like can be secured while maintaining the heat insulating effect of the present invention, and if it is 200 μm or less, high visibility and transparency can be maintained.
[0045] As described above, the transparent heat insulating adhesive layer contains 0.07% by mass or more of silica-shelled hollow microparticles based on the total solid content of the transparent heat insulating adhesive layer excluding the silica-shelled hollow microparticles. By containing 0.07% by mass or more of silica-shelled hollow microparticles based on the total solid content of the transparent heat insulating adhesive layer excluding the silica-shelled hollow microparticles, the heat insulating effect of the present invention can be obtained. In addition, it is preferable that the transparent heat insulating adhesive layer contains 0.07% to 1.7% by mass of silica-shelled hollow microparticles based on the total solid content of the transparent heat insulating adhesive layer excluding the silica-shelled hollow microparticles. If the content of silica-shelled hollow microparticles is 1.7% by mass or less based on the total solid content of the transparent heat insulating adhesive layer excluding the silica-shelled hollow microparticles, high visibility and transparency can be maintained.
[0046] <Transparent heat insulating resin layer and transparent resin> The transparent resin of the transparent heat insulating resin layer used in the transparent heat insulating film for windows of the present invention is not particularly limited in type as long as it is transparent and transmits far infrared rays, and can be adhered to the substrate film surface. For example, any resin such as acrylic resin, urethane resin, silicone resin, etc. can be used, but considering the dispersibility of the hollow particles of silica shell, acrylic resin is particularly preferably used.
[0047] The transparent resin may be used alone or in combination of two or more kinds. In addition, other components such as an ultraviolet absorber, an infrared shielding agent, a plasticizer, a photopolymerizable compound, a photoinitiator, a foaming agent, a polymerization inhibitor, an antiaging agent, a filler, a coupling agent, and an antistatic agent may be added within a range that does not impair the object of the present invention.
[0048] As described above, the thickness of the transparent heat insulating resin layer is preferably 10 to 200 μm, more preferably 20 to 100 μm. If the thickness of the transparent heat insulating adhesive layer is 10 μm or more, the heat insulating effect of the present invention is maintained while the adhesive strength with glass or the like is ensured, and if it is 200 μm or less, high visibility and transparency can be maintained.
[0049] As described above, the transparent heat insulating resin layer contains 0.07% by mass or more of silica-shelled hollow fine particles based on the total solid content of the transparent heat insulating resin layer excluding the silica-shelled hollow fine particles. By containing 0.07% by mass or more of silica-shelled hollow fine particles based on the total solid content of the transparent heat insulating resin layer excluding the silica-shelled hollow fine particles, the heat insulating effect of the present invention can be obtained. In addition, it is preferable that the content of silica-shelled hollow fine particles is 0.07% by mass to 1.7% by mass based on the total solid content of the transparent heat insulating resin layer excluding the silica-shelled hollow fine particles. If the content of silica-shelled hollow fine particles is 1.7% by mass or less based on the total solid content of the transparent heat insulating resin layer excluding the silica-shelled hollow fine particles, high visibility and transparency can be maintained. EXAMPLES
[0050] Example 1 The internal space is divided into 65 nm, which is smaller than 68 nm, and the thermal conductivity is 0.02 W / m K. Silica-shelled hollow particles "SUFA" manufactured by TM Factory Co., Ltd. were sieved to have an average outer diameter of 32.8 μm (outer diameter range: spherical equivalent diameter (volume basis) 3.0 μm to 51.2 μm, measured with a laser diffraction / scattering type particle size distribution measuring device LA-950V2 manufactured by HORIBA, Ltd.). The silica-shelled hollow particles were dispersed in the adhesive "SK Dyne" manufactured by Soken Chemical & Engineering Co., Ltd. at 0.05 mass%, 0.1 mass%, 0.7 mass%, 1.3 mass%, and 2.0 mass% relative to the solid content. The prepared adhesive was laminated to a thickness of 25 μm on a PET film measuring 25 cm × 25 cm and 50 μm in thickness. Then, six pieces of PET film each laminated with 25 μm of adhesive were attached to a 25 cm × 25 cm, 3 mm thick glass plate in the following manner. (1) A 3 mm thick glass plate with a PET film that does not contain hollow silica shell particles in the adhesive (2) A 3 mm thick glass plate attached with a PET film containing 0.05% by mass of hollow silica-shelled particles with an average outer diameter of 32.8 μm in the adhesive. (3) A 3 mm thick glass plate attached with a PET film containing 0.1% by mass of hollow silica-shelled particles with an average outer diameter of 32.8 μm in the adhesive. (4) A 3 mm thick plate glass to which a PET film containing 0.7% by mass of hollow silica-shelled particles with an average outer diameter of 32.8 μm has been attached. (5) A 3 mm thick plate glass to which a PET film containing 1.3% by mass of hollow silica-shelled particles with an average outer diameter of 32.8 μm has been attached. (6) A 3 mm thick plate glass to which a PET film containing 2.0% by mass of hollow silica-shelled particles with an average outer diameter of 32.8 μm has been attached.
[0051] Next, six 25 x 25 x 25 cm boxes with one side open were created using 5 mm thick polystyrene foam boards as measurement devices. With the openings of the boxes facing upwards, a corkboard was placed in the center of the lower inside of the boxes, a ceramic board was placed on top of that, a 100 V / 150 W heater was placed on top of that as a heat source, and a 6 x 6 cm heat sink was placed on top of that, and the sensor part of the thermocouple that measures the temperature inside the box was covered with aluminum foil and placed in the center of the box. Next, the 3 mm thick glass plate with the PET film prepared above attached was attached to the opening of a 5 mm thick polystyrene foam box, with the film surface facing inward. Next, the polystyrene foam boxes with the glass plates attached to them were placed with the glass surface facing up and placed in a room set to 18°C. The heater was then turned on to heat the inside of the box, and the temperature was measured when the temperature inside the box reached a steady state. The applied power at this time was 32.1 W. The haze value at that time was determined according to JIS K7136 using a spectroscopic haze meter (SH7000) manufactured by Nippon Denshoku Industries Co., Ltd. The results are shown in Table 1.
[0052] [Table 1]
[0053] When heated by a heater, the temperature inside the box of a 3 mm thick plate glass attached with a PET film laminated with an adhesive containing 0.07% or more by mass of hollow silica-shelled particles with an average outer diameter of 32.8 μm was 3.5°C to 5.4°C higher than that of a plate glass attached with a PET film laminated with an adhesive that does not contain hollow silica-shelled particles, and it is found that the adhesive layer of the present invention containing 0.07% or more by mass of hollow silica-shelled particles relative to the adhesive has a heat insulating effect. Note that in this example, the effect of the present invention was confirmed by partitioning at 65 nm, which is close to the mean free path of air 68 nm, and if the partition distance is smaller than this, heat exchange due to gas convection or molecular motion does not occur as described above (described in paragraphs 0032 to 0033), and the heat insulating effect is further improved.
[0054] It is also found that if the content of hollow particles having a silica shell is 1.7% by mass or less, the haze value is small and high visibility and transparency can be maintained. Therefore, the content of hollow particles having a silica shell is preferably 0.07% by mass to 1.7% by mass.
[0055] Example 2 The internal space is divided into 65 nm particles, smaller than 68 nm, and "SUFA", a silica shelled hollow particle manufactured by TM Factory Co., Ltd., with a thermal conductivity of 0.02 W / m K, was sieved to classify the particle sizes into average outer diameters of 5.1 μm, 12.3 μm, 32.8 μm, 50.2 μm, and 60.7 μm, and each was dispersed at 0.1 mass% in the solid content of the adhesive. The prepared adhesive was laminated to a thickness of 25 μm on a PET film measuring 25 cm × 25 cm and 50 μm in thickness. Then, six pieces of PET film each laminated with 25 μm of adhesive were attached to a 25 cm × 25 cm, 3 mm thick glass plate in the following manner. (7) A 3 mm thick plate glass with a PET film attached to it that does not contain hollow silica shell particles in the adhesive. (8) A 3 mm thick plate glass to which a PET film containing 0.1% by mass of hollow silica-shelled particles with an average outer diameter of 5.1 μm has been attached. (9) A 3 mm thick plate glass to which a PET film containing 0.1% by mass of hollow silica-shelled particles with an average outer diameter of 12.3 μm has been attached. (10) A 3 mm thick plate glass to which a PET film containing 0.1% by mass of hollow silica-shelled particles with an average outer diameter of 32.8 μm has been attached. (11) A 3 mm thick plate glass to which a PET film containing 0.1% by mass of hollow silica-shelled particles with an average outer diameter of 50.2 μm is attached. (12) A 3 mm thick plate glass to which a PET film containing 0.1% by mass of hollow silica-shelled particles with an average outer diameter of 60.7 μm has been attached.
[0056] Next, six 25 x 25 x 25 cm boxes with one side open were created using 5 mm thick polystyrene foam boards as measurement devices. With the openings of the boxes facing upwards, a corkboard was placed in the center of the lower inside of the boxes, a ceramic board was placed on top of that, a 100 V / 150 W heater was placed on top of that as a heat source, and a 6 x 6 cm heat sink was placed on top of that, and the sensor part of the thermocouple that measures the temperature inside the box was covered with aluminum foil and placed in the center of the box. Next, the 3 mm thick glass plate with the PET film prepared above attached was attached to the opening of a 5 mm thick polystyrene foam box, with the film surface facing inward. Next, the polystyrene foam boxes with the glass plates attached to them were placed with the glass surface facing up and placed in a room set to 18°C. The heater was then turned on to heat the inside of the box, and the temperature was measured when the temperature inside the box reached a steady state. The applied power at this time was 32.1 W. The haze value at that time was determined according to JIS K7136 using a spectroscopic haze meter (SH7000) manufactured by Nippon Denshoku Industries Co., Ltd. The results are shown in Table 2.
[0057] [Table 2]
[0058] When heated using a heater, the steady-state temperature inside the box for a 3 mm thick glass plate attached with a PET film laminated with an adhesive containing 0.1 mass% of silica-shelled hollow microparticles with an average outer diameter of 3 μm or more was 3.5°C to 4.9°C higher than that of a glass plate attached with a PET film laminated with an adhesive that did not contain silica-shelled hollow microparticles.
[0059] It is also found that if the average outer diameter of the silica-shelled hollow fine particles contained in the adhesive is 55 μm or less, the haze value is small and high visibility and transparency can be maintained. Therefore, the average outer diameter of the silica-shelled hollow fine particles is preferably 3 μm to 55 μm, more preferably 5 μm to 45 μm, and most preferably 5 μm to 35 μm.
[0060] As described above, it is clear that the present invention can provide a transparent heat insulating film for windows that is excellent in mechanical strength and has a sufficient heat insulating effect. [Explanation of symbols]
[0061] 1. Base film 2. Adhesive 3. Silica-shelled hollow particles 4 Transparent heat insulating adhesive layer 5 Hard Coat Layer 10 Transparent window insulation film 11 Base film 12 Transparent resin 13. Silica-shelled hollow particles 14 Transparent insulating resin layer 15 Hard coat layer 16 Adhesive layer 20 Transparent window insulation film
Claims
1. A transparent heat insulating film for windows, which is a transparent heat insulating film for bonding to a glass substrate for windows, a heat insulating layer in which hollow particles having a silica shell are dispersed on at least one surface of a substrate film that transmits far-infrared rays, the internal space of the hollow particles being approximately uniformly divided into spaces of 68 nm or less, the hollow particles having a silica shell being dispersed in an amount of 0.07 mass% or more based on the total amount of solids in the heat insulating layer excluding the hollow particles having a silica shell; The heat insulating layer is a transparent heat insulating adhesive layer that transmits far infrared rays, A transparent heat insulating film for windows, characterized in that the average outer diameter of the hollow fine particles having a silica shell is 3 μm to 55 μm, and the hollow fine particles are dispersed in the transparent heat insulating adhesive layer at 0.07 mass % to 1.7 mass % based on the total solid content excluding the hollow fine particles having a silica shell.
2. A transparent heat insulating film for windows, which is a transparent heat insulating film for bonding to a glass substrate for windows, a heat insulating layer in which hollow particles having a silica shell are dispersed on at least one surface of a substrate film that transmits far-infrared rays, the internal space of the hollow particles being approximately uniformly divided into spaces of 68 nm or less, the hollow particles having a silica shell being dispersed in an amount of 0.07 mass% or more based on the total amount of solids in the heat insulating layer excluding the hollow particles having a silica shell; The heat insulating layer is a transparent heat insulating resin layer that transmits far infrared rays, A transparent heat insulating film for windows, characterized in that the average outer diameter of the hollow fine particles having a silica shell is 3 μm to 55 μm, and the hollow fine particles are dispersed in an amount of 0.07 mass % to 1.7 mass % based on the total solid content of the transparent heat insulating resin layer excluding the hollow fine particles having a silica shell.
3. 3. The transparent heat insulating film for windows according to claim 1, wherein the heat insulating layer has a thickness of 10 to 200 μm.
Citation Information
Patent Citations
Adiabatic substance and method of its manufacture
JP1976142017A
Electric discharge lamp
JP1983010361A
Cavitation detecting device for pump
JP1989045975A
Heat shielding insulation film
JP2012056138A
Functional fabric and method for producing the same
JP2018519196A